One day in December : Celia Sánchez and the Cuban Revolution - Stout, Nancy (Monthly Review Press, 2013)
"Celia Sánchez is the missing actor of the Cuban Revolution. Although not as well known in the English-speaking world as Fidel Castro and Che Guevara, Sánchez played a pivotal role in launching the revolution and administering the revolutionary state. She joined the clandestine 26th of July Movement and went on to choose the landing site of the Granma and fight with the rebels in the Sierra Maestra. She collected the documents that would form the official archives of the revolution, and, after its victory, launched numerous projects that enriched the lives of many Cubans, from parks to literacy programs to helping develop the Cohiba cigar brand. All the while, she maintained a close relationship with Fidel Castro that lasted until her death in 1980. The product of ten years of original research, this biography draws on interviews with Sánchez's friends, family, and comrades in the rebel army, along with countless letters and documents. Biographer Nancy Stout was initially barred from the official archives, but, in a remarkable twist, was granted access by Fidel Castro himself, impressed as he was with Stout's project and aware that Sánchez deserved a worthy biography. This is the extraordinary story of an extraordinary woman who exemplified the very best values of the Cuban Revolution: selfless dedication to the people, courage in the face of grave danger, and the desire to transform society"--Publisher's description.